Prevalence and quality-of-life burden of vasomotor symptoms associated with menopause: A European cross-sectional survey. (January 2023) - Nappi, Rossella E.; Siddiqui, Emad; Todorova, Lora; Rea, Carol; Gemmen, Eric; Schultz, Neil M.
Highlights: A high proportion of postmenopausal women reported experiencing moderate-to-severe vasomotor symptoms in this European survey. The severity of vasomotor symptoms was greatest among Italian and lowest among French women. The most common symptom was "feeling tired and worn out". Weight gain was the overall most bothersome symptom. Only a small proportion of survey participants had been treated for menopausal symptoms. Abstract: Objectives: To determine, in a European cohort, the prevalence and health-related quality-of-life (QOL) burden of moderate-to-severe vasomotor symptoms (VMS) in postmenopausal women, and among subgroups of women not taking hormone therapy (HT). Study design: Screening surveys were sent to a random sample of women aged 40–65 years; those meeting the inclusion criteria completed the full questionnaire. Women with successfully treated VMS or breast cancer or who were receiving HT for medical conditions were excluded. Main outcome measures: Frequency and duration of VMS, perceptions of menopause, seeking advice from a healthcare professional, treatment for VMS symptoms, perceptions of HT use, out-of-pocket costs, and other approaches to coping with menopause. The Menopause-Specific QOL (MENQOL) questionnaire and Work Productivity and Activity Impairment (WPAI) questionnaire were included. Results: Of 11, 452 women who completed the screening survey, 5178 were postmenopausal and 2035 completed the full questionnaire. Prevalence of moderate-to-severe VMS ranged from 31 % in France to 52 % in Italy. The majority were in the HT-caution or HT-averse group, despite being eligible for HT. Most common menopausal symptoms reported in the MENQOL were "feeling tired or worn out, " with aching in muscles and joints reported as the most common symptom in Spain. Weight gain was the most bothersome symptom in all countries, except for Spain, where low backache was more bothersome. Hot flashes and night sweats had a greater impact on daily than on working activities, as measured by the WPAI. Conclusions: A high proportion of European women reported experiencing moderate-to-severe VMS, with associated symptoms influencing QOL.